A current literature review of international mediation. Issue 1 (2014) - ,
Abstract : Purpose – A rapidly expanding body of literature on international mediation, as well as the central role international mediation plays in modern‐day conflict resolution, make it necessary to review and analyze this vastly evolving field of study. This study seeks to review the most significant trends and debates in the literature on international mediation, with an emphasis on the literature of the past six years.Design/methodology/approach – Reflecting Wall et al. 's staged conceptualization of the mediation process; this review essay is divided in three sections that cover the antecedents of mediation, possible mediation approaches, and the outcomes these approaches yield – making it possible to review and analyze the diverse sets of theories within the field of mediation, as well the various methodological approaches employed to test these theories.Findings – Much research to date has focused on how international mediation in armed conflicts affects the likelihood of reaching a negotiated agreement, while other possible outcomes of mediation have been understudied. Accordingly, research needs to be done on the effects of mediation attempts that did not lead to a peace agreement, as well as the accumulative effect of peace agreements. Furthermore, the relation between negative peace and mediation has been studied extensively, but how mediation affects the degree of positive peace has received scant scholarly attention. Finally, the interlinkages between the different phases of the mediation process need to be examined more extensively.Originality/value – This review identifies the state of the art knowledge concerning the international mediation process, which allows peacemakers to make informed decisions in order to prevent and resolve armed conflict in the twenty‐first century.